STUDY ON THE EFFECT OF BIOOXIDATION OF CLAY TYPE GOLD WASTE MINERAL USING Bacillus aryabhattai STRAIN SKC-5 ON GOLD RECOVERY THROUGH CYANIDATION - Erninzafitri, Nandira
Considering the decrease of the non-refractory gold ore availability, the refractory gold ore began to be processed. However, to process refractory gold ore, a pretreatment process is needed to increase the gold extraction which leads to the biooxidation development. In this study, biooxidation experiment was investigated on clay-type gold waste mineral that is mineral part of overburden, precisely in the core soil layer which contains gold as well as impurity minerals such as sulfide, carbonate, and clay minerals using iron- and sulfur-oxidizing bacteria.. A series of experiments was first started with ore grinding using a Ball Mill, followed by sieving to obtain a particle size of passing 75 microns (-75 ?m). Later, the ore was homogenized and sampled for the purposes of characterization and biooxidation experiments. Prior to biooxidation experiments, a bacterial growth curve was constructed to determine the optimum incubation time of bacteria used for the next experiment. Direct cyanidation experiment was also carried out to the ore without biooxidation to determine the effect of the biooxidation process in increasing the gold extraction. Then, a preliminary biooxidation experiment was conducted to determine the most optimum bacteria. After that, core biooxidation experiments were carried out with the most optimum bacteria with several variations including bacterial inoculum concentration, pyrite (FeS2) concentration, and iron sulfate (FeSO4.7H2O) concentration. The results showed that the refractory gold ore dominantly contained quartz and calcite mineral as ore impurities. The gold particles were micro-sized and included in sulfide minerals. The percent of preg-robbing of the gold ore obtained is 72,55%. Gold extraction after direct cyanidation was approximately 76,57%. The preliminary biooxidation experiment using the most optimum was able to enhance the gold extraction up to 88,61%. Optimization of biooxidation experiment has significantly increase the gold extraction about 90,37% under the most optimum conditions : 5% (v/v) bacterial inoculum, 9 g/l pyrite (FeS2), and 6,7 g/l iron sulfide (FeSO4.7H2O). This study suggested that biooxidation pre-treatment has been proven as a low-cost and environmentally friendly method to enhance the gold extraction for the refractory gold ore and thus, is potentially applicable to the field scale with further optimization.